Slownik angielsko-polski dla informatykow - Szaniawski, Jacek; Marciniak, Marian (Warszawa : ArsKom, 1994)
An English/Polish dictionary for users of computers and information science.
Previous ed. by Marian Marciniak and Jacek Szaniawski.
Keywords: Information science -- Dictionaries; English language -- Dictionaries -- Polish